Pelatihan Dalam Menetapkan Strategi Komunikasi Pemasaran Yang Tepat Untuk Produk Dan Jasa dari UKM - Luki Adiati Pratomo; Lavlimatria Esya; Ayu Ekasari; Ulfi Naria Rahmawati; Wanggi Citra Ameliana (Jurnal Pengabdian Masyarakat Madani, 2021)
The COVID-19 pandemic has caused difficulties for small and medium-sized entrepreneurs, including students of the Bina Amanah Cordova School of Entrepreneurship which is a free diploma 1 (D1) school. SKBAC students or students are mostly young entrepreneurs or prospective entrepreneurs who are currently experiencing difficulties such as declining sales and even being forced to close due to COVID-19. One of the causes of the decline in sales is the difficulty of communicating with consumers considering that people choose not to leave their homes for shopping. For this reason, training on marketing communication strategies is carried out so that they can develop effective marketing communication strategies in reaching their target consumers. The method in carrying out training activities is to provide counseling to students. The counselors explain some of the tools that can be used in marketing communications such as advertising, sales promotion, events and experiences, direct marketing, publications, social media marketing, and personal selling. The results of this training show that students begin to understand the importance of marketing communication, can develop appropriate marketing communication strategies and can choose the right communication tools, one of which is social media marketing.